The Alignment Horizontal Design of Alternative Road: A Case of Jalan Subang – Cikamurang, West Java - Muhammad Rifqiawan Farid; Andri Irfan Rifai; Mohamad Taufik (International Journal Labs, 2022)
Horizontal alignment belongs to the aspect of the geometric design of the road. Jalan Subang - Cikamurang, located in Indramayu, West Java, is planned to have three horizontal alignments. This design aims to connect Subang and Cikamurang to shorten the travel time for the surrounding community's needs. This research uses the Bina Marga method, referring to the 2021 Road Geometric Design Guidelines. First, road traffic data is obtained from the google earth application and then processed with a manual method to determine the coordinates of the road traffic and the location of horizontal alignment. Then the data obtained is processed by referring to the Bina Marga method to design horizontal alignment. Jalan Subang - Cikamurang is a Primary Local Road (Arterial Road), Primary Collector, and class III C road type. Three horizontal alignments with Spiral-Circle-Spiral (SCS) type, the first horizontal alignment is at STA 0+544.018 – 0+819.445, the second horizontal alignment is at STA 1+224.778 – 1+474.695, and the third horizontal alignment is at STA 1+763 – 2+164.390.